2005
DOI: 10.1002/jbm.b.30243
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of guided nerve regeneration using progesterone‐ and pregnenolone‐loaded chitosan prostheses

Abstract: Recently, numerous guide chambers for the treatment of injured nerves made up of different biomaterials have been designed, capable of hosting living cells or carrying neurotrophic or neuroactive substances to be directly released to the injured tissue. In this study, chitosan prostheses containing neurosteroids (progesterone and pregnenolone) were used for bridging a 10-mm gap in the rabbit facial nerve. Gas chromatography was used to quantify neurosteroid content in the prostheses prior to and after subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…These include neuroprotection against ischemia and stroke (Cutler, et al, 2005,Djebaili, et al, 2005,Hoffman, et al, 2003,Lapchak, 2004,Meffre, et al, 2007,Shear, et al, 2002,VanLandingham, et al, 2006, recovery of motor function after spinal cord injury (di Michele, et al, 2000,Fiore, et al, 2004,Labombarda, et al, 2006,Patte-Mensah, et al, 2004,Pomata, et al, 2000, regulation of myelination (Chavez-Delgado, et al, 2005,Gago, et al, 2001,Ghoumari, et al, 2005,Ghoumari, et al, 2003,Le Goascogne, et al, 2000,Schumacher, et al, 2000,Schumacher, et al, 2004, proliferation of neuronal stem cells (Suzuki, et al, 2004,Wang, et al, 2005 , neurogenesis in the hippocampus (Keller, et al, 2004,Suzuki, et al, 2004,Wang, et al, 2005, and induction of analgesia (Pathirathna, et al, 2005,Todorovic, et al, 2004. Many of these actions of neurosteroids are discussed in detail in other papers in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…These include neuroprotection against ischemia and stroke (Cutler, et al, 2005,Djebaili, et al, 2005,Hoffman, et al, 2003,Lapchak, 2004,Meffre, et al, 2007,Shear, et al, 2002,VanLandingham, et al, 2006, recovery of motor function after spinal cord injury (di Michele, et al, 2000,Fiore, et al, 2004,Labombarda, et al, 2006,Patte-Mensah, et al, 2004,Pomata, et al, 2000, regulation of myelination (Chavez-Delgado, et al, 2005,Gago, et al, 2001,Ghoumari, et al, 2005,Ghoumari, et al, 2003,Le Goascogne, et al, 2000,Schumacher, et al, 2000,Schumacher, et al, 2004, proliferation of neuronal stem cells (Suzuki, et al, 2004,Wang, et al, 2005 , neurogenesis in the hippocampus (Keller, et al, 2004,Suzuki, et al, 2004,Wang, et al, 2005, and induction of analgesia (Pathirathna, et al, 2005,Todorovic, et al, 2004. Many of these actions of neurosteroids are discussed in detail in other papers in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have indicated that the best results on guided regeneration of facial nerves of rabbits is obtained with P when used impregnated in biodegradable prostheses, such as chitosan [8]. In particular, the exposure to P induces, in comparison to the vehicle, an increase in the number of Schwann cell nuclei, of nonmyelinated and myelinated nerve fibers (with their respective diameters), as well as in the g ratio of myelinated nerve fibers.…”
mentioning
confidence: 99%
“…It is difficult to compare the kinematics with other studies due to the different methodologies. 3,4,30,34,36,[53][54][55][56] A previous study 4 demonstrated that when a chitosanplus-progesterone tube is implanted in sectioned peripheral facial nerves of rabbits, progesterone allows the anatomical recovery of the nerve morphology. In contrast, Rosales-Cortes et al 39 found no differences in dog sciatic nerve morphology, even when the nerves were repaired with chitosan alone or chitosan plus progesterone tubes.…”
Section: Discussionmentioning
confidence: 99%
“…14,48 In addition, chitosan has also been used for the delivery of nerve growth factors 13,14,26 and hormones. 3,4,39,40,51 Chitosan tubes impregnated with progesterone have been used for nerve repair, producing partial recovery of muscle function but inducing neuropathic pain and minimal secondary immune adverse reactions. 4,39 However, progesterone has been shown to have anti-nociceptive and neuroprotective effects on the transected trigeminal nerve 23,29 as well as to lead to reduced axonal sprouting in mice.…”
mentioning
confidence: 99%